1987
DOI: 10.1136/gut.28.1.64
|View full text |Cite
|
Sign up to set email alerts
|

Antecedent long term ethanol consumption in combination with different diets alters the severity of experimental acute pancreatitis in rats.

Abstract: SUMMARY The effect of fat rich (F), protein rich (P) and carbohydrate rich (C) diets

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…59,60 Furthermore, various combinations of ethanol and a high-fat diet worsen both caerulein-and bile acid-induced experimental acute pancreatitis. [61][62][63] Finally, the excessive ethanol consumption that often occurs in human alcoholic pancreatitis may be accompanied by decreased nutritious food intake, leading to malnourishment and an increase in fatty acid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…59,60 Furthermore, various combinations of ethanol and a high-fat diet worsen both caerulein-and bile acid-induced experimental acute pancreatitis. [61][62][63] Finally, the excessive ethanol consumption that often occurs in human alcoholic pancreatitis may be accompanied by decreased nutritious food intake, leading to malnourishment and an increase in fatty acid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Letko et al 54 used the same model to test the various modes of ethanol administration and found that it did not influence the development of acute pancreatitis. A number of other studies have found that ethanol can sensitize acinar cells to CCK‐induced procarboxypeptidase A 1 processing in vitro and can sensitize to various forms of acute pancreatitis in vivo 61–64. In this way, ethanol is thought to increase stimulation‐dependent induction of acute pancreatitis, and thus may be important in ethanol toxicity in the pancreas.…”
Section: Non‐invasive Models Of Acute Pancreatitismentioning
confidence: 96%
“…47 Animal models document associations with high protein and fat diets in the development of AP. [48][49][50][51] Further potential evidence for the role of high-fat diets in the development of AP comes from the results of a study evaluating ketogenic diets in the management of idiopathic epilepsy. 3 In that study 3/9 dogs fed a ketogenic diet (57% fat, 5.8% NFE, 25% crude protein; as dry matter) developed pancreatitis whereas only 2/31 dogs fed the control diet (16% crude fat, 54% NFE, 25% crude protein; as dry matter) developed pancreatitis.…”
Section: Dietary Factorsmentioning
confidence: 99%